2013
DOI: 10.12659/pjr.884010
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI imaging of the brain in MELAS syndrome

Abstract: SummaryBackground:MELAS syndrome (mitochondrial myopathy, encephalopathy, lactic acidosis, stroke-like episodes) is a rare, multisystem disorder which belongs to a group of mitochondrial metabolic diseases. As other diseases in this group, it is inherited in the maternal line.Case Report:In this report, we discussed a case of a 10-year-old girl with clinical and radiological picture of MELAS syndrome. We would like to describe characteristic radiological features of MELAS syndrome in CT, MRI and MR spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Focal hypodensities with atrophy are commonly seen on CT scans of childhood-onset MELAS syndrome [16], [17], [18]. Global atrophy and calcification of the basal ganglia are sometimes present [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal hypodensities with atrophy are commonly seen on CT scans of childhood-onset MELAS syndrome [16], [17], [18]. Global atrophy and calcification of the basal ganglia are sometimes present [16].…”
Section: Discussionmentioning
confidence: 99%
“…These diffusion signal abnormalities are likely to resolve over time, paralleling clinical improvement, while new lesions may develop with or without new symptoms. This migratory, waxing and waning pattern of stroke-like lesions on imaging is a cardinal feature of MELAS syndrome [16], [18], [23]. Pattern of ADC mapping is variable.…”
Section: Discussionmentioning
confidence: 99%
“…149 The characteristics of mitochondrial strokes are different from those of thrombotic events, primarily in that they do not conform to vascular territories. [150][151][152][153][154][227][228][229][230] MELAS syndrome (mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes) typically presents in a previously normal child with a history of migrainous headaches and vomiting. [230][231][232] Children with MELAS often have short stature and a history of seizures.…”
Section: Systemic Causes: Inflammatory and Genetic/metabolicmentioning
confidence: 99%
“…Yoshida et al, reported a patient with 2 episodes of status epilepticus (similar to the patient in the current report) and suggested that a more protracted course of seizures with a persistent altered mental status was concomitant with larger brain lesions ( Yoshida et al, 2013 ). On the other hand, stroke-like episodes as the most common clinical features, and the corresponding changes in brain imaging are very helpful to guide clinicians to correctly diagnose MELAS syndrome ( Pauli, Zarzycki, Krzysztalowski, & Walecka, 2013 ).…”
Section: Discussionmentioning
confidence: 99%